MANAGEMENT OF VENTILATION DISORDERS IN PATIENTS POST OP LAPARATOMY EXPLORATION DIAPHRAGM RUPTURE: CASE STUDY - ZAHRUL INSAN SISMAYADI; Etika Emaliyawati (Universitas Padjadjaran, 2022)
Introduction: A diaphragmatic rupture, which can also be called a diaphragmatic tear, is a tear that occurs in the diaphragm. The muscles at the base of the thoracic cavity play an important role when breathing. The purpose of this study is to present a nursing care plan with a focus on handling ventilation disorders in patients with diaphragmatic rupture so that it can become nursing implications in the prevention and complications of diaphragmatic rupture. Method: Researchers used the case study method which was obtained in November 2022 in the General Intensive Care Unit Room at the Hasan Sadikin General Hospital, Bandung City. Discussion: The best treatment for this diaphragmatic rupture is surgery, one of which is laparotomy, a diaphragmatic rupture will result in impaired ventilation and must be treated using a ventilator in full control. When using a ventilator, the patient's condition must always be monitored hemodynamically, especially respiration rate and oxygen saturation. The collaboration of midazolam and rocuronium drugs is useful as a sedative to make the patient drowsy and decrease anxiety. Conclusion: respiratory monitoring and drug collaboration are very useful in patients who experience impaired ventilation with a medical diagnosis of post-laparotomy exploration rupture diaphragmIntroduction: A diaphragmatic rupture, which can also be called a diaphragmatic tear, is a tear that occurs in the diaphragm. The muscles at the base of the thoracic cavity play an important role when breathing. The purpose of this study is to present a nursing care plan with a focus on handling ventilation disorders in patients with diaphragmatic rupture so that it can become nursing implications in the prevention and complications of diaphragmatic rupture. Method: Researchers used the case study method which was obtained in November 2022 in the General Intensive Care Unit Room at the Hasan Sadikin General Hospital, Bandung City. Discussion: The best treatment for this diaphragmatic rupture is surgery, one of which is laparotomy, a diaphragmatic rupture will result in impaired ventilation and must be treated using a ventilator in full control. When using a ventilator, the patient's condition must always be monitored hemodynamically, especially respiration rate and oxygen saturation. The collaboration of midazolam and rocuronium drugs is useful as a sedative to make the patient drowsy and decrease anxiety. Conclusion: respiratory monitoring and drug collaboration are very useful in patients who experience impaired ventilation with a medical diagnosis of post-laparotomy exploration rupture diaphragm